Pengaruh Yoga Menstruasi Terhadap Penurunan Dismenore Primer Pada Remaja Putri - Nurlela, Lela; Hilmiah, Hilmiah (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Primary dysmenorrhea is a common problem experienced by adolescent girls, characterized by lower abdominal pain during menstruation without any organic abnormalities. One non-pharmacological intervention that is gaining popularity is menstrual yoga. Objective: To determine the effect of menstrual yoga on reducing the level of primary dysmenorrhea in adolescent girls. Methods: This study used a quasi-experimental design with a pretest-posttest approach with a control group. The sample consisted of 60 female students experiencing primary dysmenorrhea, divided into an intervention group (menstrual yoga) and a control group. The intervention was conducted for 4 weeks, 3 times per week, for 30 minutes each. Pain was measured using a Visual Analog Scale (VAS). Data were analyzed using the Wilcoxon and Mann-Whitney tests. Results: There was a significant reduction in dysmenorrhea pain levels in the intervention group (p<0.05), while the control group showed no significant change. Conclusion: Menstrual yoga is effective in reducing primary dysmenorrhea in adolescent girls.